The Role of Artificial Intelligence in Enhancing Professional Communication in a Foreign Language - Bulakevych, Anna; Mokhniuk, Anna (Регіональна рада молодих вчених при управлінні освіти і науки Волинської обласної державної адміністрації, 2025)
Artificial intelligence significantly enhances professional communication in foreign languages by offering tools for translation, real-time interaction, and language learning. However, AI should complement-not replace-human empathy, cultural awareness, and language skills, which remain vital for effective communication in a global workforce.
Keywords: Professional Communication; AI-driven communication tools; artificial intelligence; foreign language; technological advancements